Adaptive Learning Systems: Personalizing Mathematics Instruction for At-Risk Students - Zhang Li; Ethan Tan; Priya Patel (Journal of Paddisengeng Technology, 2026)
Background. Mathematics learning among at-risk students is frequently constrained by heterogeneous learning gaps, low engagement, and limited access to individualized instruction. Conventional teaching approaches often fail to accommodate these differences, leading to persistent disparities in academic achievement. Purpose. This study aims to examine the effectiveness of adaptive learning systems in personalizing mathematics instruction and improving learning outcomes for at-risk students, as well as to explore the role of student engagement in this process. Method. A quasi-experimental mixed-methods design was employed involving 112 students assigned to experimental (adaptive learning system) and control (traditional instruction) groups. Data were collected through pretest–posttest assessments to measure achievement, engagement questionnaires to assess behavioral and emotional involvement, and system-generated learning analytics to track progress and interaction patterns. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative insights were derived through thematic analysis. Results. The findings indicate that adaptive learning systems significantly improve mathematics achievement and student engagement compared to conventional instructional methods. Personalized learning pathways, immediate feedback, and continuous progress monitoring contribute to enhanced performance and reduced variability among learners. Engagement is identified as a mediating factor that strengthens the relationship between adaptive instruction and academic achievement. Conclusion. Adaptive learning systems offer an effective and scalable solution for supporting at-risk students in mathematics education. The results underscore the importance of integrating personalization and engagement-focused strategies to promote equitable learning outcomes. Educators and institutions are encouraged to adopt adaptive technologies to create more responsive and inclusive instructional environments.